PENERAPAN PERBUATAN MELANGGAR HUKUM DALAM RANGKA MEMBERIKAN PERLINDUNGAN HUKUM ATAS LAGU RAKYAT â€œTILLO-TILLO DAN ALATIPANGâ€ - Iristian, Yovan (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2012)
ABSTRACTThe policy to determine the copyright holder on the song unknown its creator according to the Copyright Acts in Indonesia is performed by the State, in which the State holds that copyright consistently based on article 11 paragraph (3) of the Acts Number 19 of 2002 about copyright. The copyright is held by the State and to be the collective property. The protection period is without period of time or unlimited, in which the state is holding the copyright consistently. In Indonesia, the period of time for copyright protection generally is along the life of its creator plus 50 years or 50 years after for the first time it notified or published. This case conducted recalled the developments in trade, industry, and investment fields already such rapid, until need the protection increase for the Creator and Owner of the Related Right by keep pay attention to the vast society interest. The efforts reached for the law enforcement to the infringement to copyright on the song whose creator is unknown is by performing law enforcement based on the Acts Number 19 of 2002 about the copyright in Indonesia. In Chapter XII it is arranged that, the law enforcement on copyright is performed by the copyright holder in the civil law, but there is also the criminal law side.Key Words: Creator, Song Copyright